Effectiveness of a curriculum-based educational intervention on oral health behavior and dental caries experience among Indian schoolchildren - Vineetha Karuveettil; S Vijay Kumar; Chandrashekar Janakiram; Joe Joseph (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: The high incidence of dental diseases among Indian children can be attributed to low awareness regarding the oral health maintenance. The school health curriculum in India is deficient of an oral health component, and there are no organized oral health programs for schoolchildren existing at present. Therefore, the present study was conducted to assess the effectiveness of an oral health curriculum in improving the oral health behavior and dental caries experience in schoolchildren. METHODS: A nonrandomized trial with pretest/posttest design was conducted among 600 schoolchildren. Two intervention arms were designed with one group receiving health education from a dental health professional and other from a school teacher. The oral health curriculum was customized for three sections of different age groups (lower primary [LP], upper primary [UP], high school [HS]) and implemented for a period of 1 year. Oral health behaviors were recorded using a Knowledge, Attitude and Practice (KAP) questionnaire and were evaluated at baseline, 6 months, and 1 year of the educational intervention. Dental caries experience was measured Pre and Post - intervention using deft and decayed, missing, and filled teeth indices. Descriptive statistics were calculated for continuous data, and the change in KAP scores and dental caries experience was analyzed using the repeated measures of ANOVA, independent t-tests, and paired t-tests. RESULTS: There were significant improvements in KAP regarding oral health among Indian schoolchildren. Significant reductions in decayed primary teeth were observed in LP and UP schoolchildren post-intervention. However, there was no significant difference in primary outcome between the two intervention arms. CONCLUSIONS: A curriculum-based health education intervention customized for different age groups was found to be effective in improving oral health behavior and dental caries experience among Indian schoolchildren.